Pengaruh Pendapatan Perkapita dan Jumlah Penduduk Terhadap Tingkat Kemiskinan di Kabupaten Bone Bolango Provinsi Gorontalo - Wantogia, Misnawaty; Zainuri, Ahmad; Yusuf, Daud; Kumaji, Syam S; SM, Farid; Dunggio, Iswan; Rahim, Sukirman (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the effect of per capita income on poverty levels in Bone Bolango Regency, Gorontalo Province. The regency faces challenges in reducing poverty despite various government programs. The knowledge gap regarding the direct contribution of per capita income to poverty is the focus of this research. Here, we demonstrate that an increase in per capita income has a negative correlation with poverty levels, where each rise in income is associated with a significant reduction in poverty percentage. However, the study also found that population growth significantly increases poverty if not accompanied by improvements in economic and social infrastructure. The findings of this research imply that economic policies aimed at increasing income must be supported by improvements in access to education, healthcare, and infrastructure to more effectively reduce poverty rates in the region. Future research is expected to deepen the analysis of other factors that influence poverty more comprehensively